2014
DOI: 10.1007/s12630-014-0111-3
|View full text |Cite|
|
Sign up to set email alerts
|

The utility of transthoracic echocardiography to confirm central line placement: An observational study

Abstract: Transthoracic echocardiography [corrected] is a feasible, noninvasive, and potentially useful method to confirm appropriate placement of the guidewire before dilation and cannulation of the IJV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…Other novel tests include- fluoroscopy, chest radiography with simultaneous injection of contrast, and trans-esophageal echocardiography (TEE) to identify guidewire in the right atrium. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…Other novel tests include- fluoroscopy, chest radiography with simultaneous injection of contrast, and trans-esophageal echocardiography (TEE) to identify guidewire in the right atrium. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…In a similar fashion, Arellano et al 5 reported the utility of transthoracic echocardiography (TTE) for confirming the location of the guidewire in the RA before dilation and cannulation of the IJV. Nevertheless, the disadvantage of using TTE for guidewire confirmation is the need for sterile preparation of another ultrasound probe, expertise to perform TTE, and additional time to complete the procedure.…”
Section: To the Editormentioning
confidence: 91%
“…214,215 Observational studies also demonstrate that transthoracic ultrasound can confirm residence of the guidewire in the venous system (Category B3-B evidence). [216][217][218][219] One observational study indicates that transesophageal echocardiography can be used to identify guidewire position (Category B3-B evidence), 220 and case reports document similar findings (Category B4-B evidence). 221,222 Observational studies indicate that transthoracic ultrasound can confirm correct catheter tip position (Category B2-B evidence).…”
Section: Catheter Maintenancementioning
confidence: 95%